Contrato psicológico y compromiso organizacional: un estudio bibliométrico. - Herrera-Ballesteros, Juan; De-las-Heras-Rosas, Carlos Javier (Universitat Rovira i Virgili, 2020)
The literature on employment contains a multitude of works related to the concepts of psychological contract and organizational commitment. The level of causal relationship that both concepts have has been demonstrated, as has their importance regarding the efficiency of business organizations. The objective of this study is to examine the existing scientific literature, to study in depth the predominant approaches and to indentify which ones remain to be explored. This has been achieved by a bibliometric study. A total of 372 articles from journals catalogued in the Social Science Citation Index (SSCI), Science Citation Index Expanded (SCI-EXPANDED) and Scopus have been analyzed in detail. The application of bibliometric techniques has made it possible to analyze and present the evolution of publications in this field, by means of activity and relationship indicators. The results obtained suggest that the psychological contract and organizational commitment remain topics of interest, although no significant increase is expected. The study has verified that the literature has addressed the most important questions regarding the psychological contract and organizational commitment in business organizations; however, sensitive issues such as diversity management, impact on gender equality or aspects of organizational culture have received little attention
Keywords: Recursos humanos; Gestión de personal; Eficacia organizacional; Motivación en el trabajo; HR management; Business organizations; Motivational factors; Organizational efficiency; Diversity